(untitled) (Medico Legal Update, 2021)
This cross-sectional study has been conducted in the Bangabandhu Sheikh Mujib Medical University Gynaecology and Obstetrics Division on 72 patients who have been admitted from December 2018 to March 2019, in order to find out the percentage of pregnancy-induced high blood pressure among pregnant mothers. Of the 72 patients, 25(34.7%) have been diagnosed with pre-eclamptictoxaemia 27(37.1%) induced pregnancy and 20(27.8%) with eclampsia. Most people were 21-25 years old and their average age was 25.3 years old. Of the 72 patients, 38 were primipara (52.8 percent). 20 (27.8%) of newborns were delivered before 37 weeks, while 52 (72,2%) were delivered before 37 weeks. A cesarean section was available in 37 of all patients (51 percent). The cesarean portion in PIH & PET was higher. Of the 72 newborn patients 16(22.2%) were low in birth weight, and patients with ecclampsy were more likely to experience low birth weight. 35 of 72 patients had poor fetal results, including 1.4 percent perinatal and 33.3 percent asphyxiated infants. Only 5 (6.5 percent) had complications in maternal outcomes such as strokes, renal eclampsia. All participants in this study are women who are pregnant and receive prenatal care. WHO normally recommends patients with an antecedent of antenatal treatment less than 4 times eclampsia. In patients with eclampsia it is more common to see low birth weight, pre-term delivery and the complication for prenatal mortality.